INTEGRATION OF AQIDAH AND BUSINESS ECONOMICS IN MODERN LIFE - Anzaikhan, M. (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2025)
This study aims to analyze the concept of integration between aqidah (Islamic creed) and business economics in the context of modern life. Specifically, this research seeks to explore how the principles of aqidah in Islam can be applied in business economic practices and their role in shaping a just, sustainable, and blessed economic system. Additionally, this study identifies the challenges faced by Muslims in maintaining aqidah values amidst the rapid development of the global economy and the dominance of conventional economic systems. The method used in this research is a literature study with a descriptive analysis approach. The primary sources used are scientific journals and prominent books discussing the integration of aqidah and business economics in Islam. The results show that although aqidah plays a very important role in forming the ethical foundation and business principles in Islam, the implementation of integration between aqidah and economics still faces many challenges. The main obstacles found are the lack of understanding among Muslims regarding the basic concepts of aqidah-based economics and difficulties in applying sharia principles in modern business practices.